Gênero publicidade : entendendo as relações dialógicas na construção do sentido do texto - Kunert, Vanessa Vitali (2008)
Publicitary texts are the object of study of this work. This discursive genre seductive and persuasive is observed from an analytical perspective that goes beyond the formal aspects that make its structure, observing the way and functioning of its language as a social and dialogical practice. Thus, the study of the texts that are the corpus of this work relates to an approach to language understood as discourse, therefore belonging to a subject who takes words and utters a dialogue towards his interlocutors. Such enunciative approach is in accordance with the ideas of the Russian philosopher Mikhail Mikhailovitch Bakhtin concerning the dialogical nature of language and the notion of discursive genres, which implies that beyond the linguistic structure there are dialogical and ideological threads linked to words. Furthermore, as publicity was the genre chosen for the analysis, emphasis is given to readings that embrace such theoretical-investigative field, in order to define this genre and recognise the elements that organize it. The aim of this study is to understand the relation between text and context in the construction of meaning of publicitary texts, as well as to recognise that, in the visualisation of the linguistic and the non-linguistic component, there is a dialogue between a (I) and a (you) that is constitutive of publicity and reveals a response to other discourses that are present in the media